Development of Threat Evaluation Tool for Distributed Network Environment - Han, Keun Hee; Kim, Il Gon; Lee, Kang Won; Choi, Jin Young; Jeon, Sang Hun (Computing and Informatics, 2012)
Current information protection systems only detect and warn against individual intrusion, and are not able to provide a collective and synthesized alert message. In this paper, we propose a new Meta-IDS system which is called ``SIA System''. The SIA system can filter redundant alert messages, analyze mixed attacks using correlation alert messages from each sensor and respond to security threats quickly, after classifying them into one of four different statuses. Then we implement the SIA system and test the efficiency of it in the managed networks. Thus we confirm that the SIA system enables security managers to deal with security threats efficiently.